Bioinformatics in the Era of Post Genomics and Big Data 2018
DOI: 10.5772/intechopen.75970
|View full text |Cite
|
Sign up to set email alerts
|

Developing Network-Based Systems Toxicology by Combining Transcriptomics Data with Literature Mining and Multiscale Quantitative Modeling

Abstract: We describe how the genome-wide transcriptional profiling can be used in networkbased systems toxicology, an approach leveraging biological networks for assessing the health risks of exposure to chemical compounds. Driven by the technological advances changing the ways in which data are generated, systems toxicology has allowed traditional toxicity endpoints to be enhanced with far deeper levels of analysis. In combination, new experimental and computational methods have offered the potential for more effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Systems biology relies on the principle that connections store more information than isolated pathways or gene sets [12]. We previously demonstrated that different transcriptomic profiles in response to nanoparticulate share similar regulatory mechanisms [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems biology relies on the principle that connections store more information than isolated pathways or gene sets [12]. We previously demonstrated that different transcriptomic profiles in response to nanoparticulate share similar regulatory mechanisms [6].…”
Section: Resultsmentioning
confidence: 99%
“…We previously described a systems toxicology approach for ENM grouping and prioritisation, demonstrating that including molecular alterations of biological systems after the exposure provides better molecular proxies of toxicity [11]. However, traditional approaches in mechanistic toxicogenomics do not explicitly require modelling the interactions between genes, and are based on the assessment of a linear representation of the response [12]. Established methods to characterise chemicals mechanism of action (MOA) using omics data, preprocess and filter data in order to select the most relevant alterations and characterise them functionally.…”
Section: Introductionmentioning
confidence: 99%